2002
DOI: 10.1034/j.1600-0846.2002.080107.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of skin friction using africtional feel analyzer

Abstract: Human skin surface friction was measured by using a KES-SE Frictional Analyzer. Judging from the correlation between either MIU or MMD and sensory evaluation, we considered this instrumental analysis to be useful for evaluating the tactile impression of human skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 17 publications
6
71
2
8
Order By: Relevance
“…A constante pesquisa do tecido cutâneo e do emprego de metodologias não-invasivas tem dado origem a diferentes equipamentos para a avaliação dos efeitos dos produtos dermocosméticos (Dikes, 2002;Es-Spiekman, Lucassen, 2000;Smith et al, 2002;Oba et al, 2002;Egawa et al, 2002;Rodrigues, 1997;Zhai et al, 2008, Chilcott, Farrar, 2008, Campos et al, 2008Dujardin et al, 2002).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…A constante pesquisa do tecido cutâneo e do emprego de metodologias não-invasivas tem dado origem a diferentes equipamentos para a avaliação dos efeitos dos produtos dermocosméticos (Dikes, 2002;Es-Spiekman, Lucassen, 2000;Smith et al, 2002;Oba et al, 2002;Egawa et al, 2002;Rodrigues, 1997;Zhai et al, 2008, Chilcott, Farrar, 2008, Campos et al, 2008Dujardin et al, 2002).…”
Section: Introductionunclassified
“…M. S. Gonçalves, P. M. B. G. M. Campos 2 As técnicas de biofísica da pele são um dos mais importantes avanços tecnológicos na área da pesquisa dermatológica e tem tido repercussão nas demais áreas direta ou indiretamente a ela relacionadas. Estas técnicas consistem no estudo das características biológicas, mecânicas e funcionais da pele, por meio da medição de determinadas variáveis, por métodos não-invasivos cientificamente comprovados (Wiechers, Barlow, 2000;Pierard et al, 1995;Egawa et al, 2002;Lomuto et al, 1995;Henry et al, 1996;Oba et al, 2002;Silver et al, 2003;Le Fur, 2002;Berardesca, 1994;Benaiges et al, 1998).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The classic Amonton's law (41), which stipulates that the friction coefficient remains unchanged under varying normal loads and speeds of the probe (i.e., the opposing material used to measure the skin friction), was long challenged by numerous research works including some recent ones (36,39), in which the friction coefficient is found to be inversely proportional to load (42).…”
Section: Skin Irritation By Physical Contact/frictionmentioning
confidence: 99%
“…The UMT continuously monitored the friction force of the skin and the normal force applied by the probe to calculate the friction coefficient in realtime. Another commercial device for measuring surface properties of textile materials, a KES-SE Frictional Analyzer (38), was used in skin friction evaluation (39), where the friction coefficient (MIU) and its mean deviation (MMD) were used as the parameter to indicate surface friction. In addition, Tanaks et al launched a study on a device for monitoring skin conditions, including roughness and softness (40).…”
Section: Skin Irritation By Physical Contact/frictionmentioning
confidence: 99%